New Media - Opportunity for New and Small Parties? Political Communication before the Parliamentary Elections in Iceland in 2013 - Guðmundsson, Birgir (Veftímaritið Stjórnmál og stjórnsýsla, 2016)
This article presents results from a survey among political candidates standing in parliamentary elections in Iceland in the spring of 2013 regarding their use of media in the election campaign. The purpose of this study was twofold; first to determine the extent to which politicians have adopted new technologies. Thereby adapting their election strategies to new realities and a transformed media environment characterized by hybridization between new networked media and traditional media logic. Secondly, to examine whether in a digitalized media era, there is a difference in media use between old and new political parties. The findings suggest a process of normalization and the potential advantage for new parties, due to easier access to communication channels created by less expensive new media outlets, was by and large negated by a more complex and diverse media environment.